Efficient authentication and key distribution in wireless IP networks. - Salgarelli, L. (IEEE Wireless communications)
Emerging broadband access technologies such as 802.11 are enabling the introduction of wireless IP services to an increasing number of users. Market forecasts suggest that a new class of network providers, commonly referred to as wireless Internet service providers, will deploy public wireless networks based on these new technologies. In order to offer uninterrupted IP service combined with ubiquitous seamless mobility, these multiprovider networks need to be integrated with each other, as well as with wide-area wireless technologies such as third-generation cdma2000 and UMTS. Therefore, efficient authentication and dynamic key exchange protocols that support heterogeneous domains as well as networks with roaming agreements across trust boundaries are key to the success of wide-area wireless IP infrastructures. In this article we first describe a simple network model that accounts fro heterogeneity in network service providers, and put forward the requirements any authentication and key exchange protocol that operates in such a model should satisfy, in terms of network efficiency, security, and fraud prevention. We then introduce a new authentication and key exchange protocol, wireless shared key exchange (W-SKE). We characterize properties and limitations of the W-SKE against the requirements discussed earlier. Finally, we contrast W-SKE against other well-known and emerging approaches.